1987
DOI: 10.1901/jeab.1987.47-335
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model of Excessive Eating: Schedule‐induced Hyperphagia in Food‐satiated Rats

Abstract: Nineteen rats were maintained throughout the experiment on ad libitum wet mash and water and were trained to press a lever on fixed-interval or fixed-ratio schedules of reinforcement with electrical brain stimulation. Fourteen rats ate at least 150% more mash during intermittent reinforcement sessions than during baseline, massed reinforcement control, and/or extinction sessions. In a 3-hr session, 11 of those 14 consumed more than 22 g of wet mash (13 g dry weight), the equivalent of nearly half an animal's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…The logic is convincing, the model helps to specify the exact argument, and the data on birds document that experiencing unreliable access to food shifts the fatstorage set point upward. One study on a mammal is mentioned (Li et al 2010), but supporting data are also available from multiple species (Dionne et al 2016;Wilson & Cantor 1987). Nettle et al note the unfortunate neglect of such behavioral ecological models in the social science literature, although there is some relevant work, especially from economists (Bellisari 2008;Smith 2009).…”
Section: Randolph M Nessementioning
confidence: 99%
“…The logic is convincing, the model helps to specify the exact argument, and the data on birds document that experiencing unreliable access to food shifts the fatstorage set point upward. One study on a mammal is mentioned (Li et al 2010), but supporting data are also available from multiple species (Dionne et al 2016;Wilson & Cantor 1987). Nettle et al note the unfortunate neglect of such behavioral ecological models in the social science literature, although there is some relevant work, especially from economists (Bellisari 2008;Smith 2009).…”
Section: Randolph M Nessementioning
confidence: 99%
“…Other behaviors have been shown to be functionally similar to SIP in terms of schedule induction, including aggression and escape (Looney and Cohen 1982), excessive running (Collier and Levitsky 1968), induced stereotypy (Mittleman et al 1991), and pica (Wilson and Cantor 1987;Falk 1971). Moreover, in SIP, the substitution of water for ethanol solution-induced equivalent levels of consumption has been considered as a promising behavioral model of alcohol abuse, relating directly to the induction of compulsive alcohol drinking (Gilpin et al 2008;Mittleman et al 2003Mittleman et al , 2011Singer et al 1982;Singer and Wallace 1984;Wayner 2002).…”
Section: The Sip Proceduresmentioning
confidence: 99%
“…The phenomenon of adjunctive behavior has been documented in different animal species, including humans, and with different reinforcement schedules and types of reinforcers [19]. Other behaviors have been shown to be functionally similar to schedule-induced polydipsia, including aggression [20], excessive running [21], induced stereotypy [22] and pica [23]. Although different factors, such as the state of food deprivation or the inter-food interval length influence the SIP acquisition and expression [16] [18] [24] [25] data from our laboratory have shown that the optimal Fixed Time (FT) intervals for inducing a high rate of drinking are FT-30s [26] and FT-60s [27].…”
Section: Introductionmentioning
confidence: 99%